Geological Storage Conditions and Potential Analysis of Carbon Dioxide in the High-steep Fold Belt in Eastern Sichuan Basin - Luan Jinhua; Zhang Ruigang; Zhao Haitong; Zhang Xiong; Mao Lingling; Zhang Yi; Hu Feng; Tian Heming; Dong Yi; Jiang Liangmei; Chen Fei (E3S Web of Conferences, 2024)
Carbon sequestration refers to the technology of capturing carbon and storing it safely instead of directly discharging CO2 into the atmosphere. Rock salt is a promising CO2 reservoir, and the underground rock salt structure formed by salt cavern reservoirs in geological history has a natural sealing function. Storing carbon dioxide in salt caves can ensure that carbon dioxide is stably stored underground for a long time. However, at present, there are few studies on carbon sequestration in abandoned salt caves. This study analyses the characteristics of carbonate-evaporite strata in the high fold zone of eastern Sichuan and qualitatively evaluates Triassic carbonate-evaporite layers formed in the depth range of 800-3000 m in various sedimentary basins in Chongqing. A large set of carbonates-evaporites are developed in Chongqing, and the carbonate rocks near evaporites have low porosity and permeability, which can be used as CO2 storage caprock in salt cavities. Thick evaporated strata can also provide a good cover for CO2 storage in abandoned salt caves, which has great potential space resources.